The use of Lethabo field 2 PFA in pavement quality concrete - Gordon, Douglas (Department of Civil Engineering, 2016)
Concrete used in pavements has to be durable to withstand the load and wear imposed by vehicles moving across it and the effects of drying shrinkage and thermal changes. Failure of the pavement by either excessive cracking or degradation of the surface results in poor riding quality and low skid resistance. The inclusion of Pulverised Fuel Ash (PFA), otherwise known as fly ash, generally improves the quality of pavement concrete and thus extends its useful life. The PFA used for the thesis was from the Lethabo power station's second electrostatic precipitator field (Lethabo Field 2 PFA). This Field 2 PFA has a very close resemblance to the expected classified commercial Lethabo PFA of the future. PFA is characterised by its fineness. The Field 2 PFA had 7.7 percent retained on the 45 micron sieve. This was considerably finer than the current commercial Matla PFA with about 12 percent retained. It was thus expected that the higher quality Lethabo Field 2 PFA could be used to produce higher quality concrete. The other mix materials were those commonly used in the Western Cape. The aggregates used were Cape Flats Dune sand and Malmesbury shale (hornfels). The dune sand typically has very little fines content, causing severe bleeding problems in normal concrete mixes. The crushed coarse aggregate was 13 mm and flaky in shape. Ordinary Portland cement (OPC) was obtained from the De Hoek cement factory. The investigation was carried out in two parts. First was the development of a wide range of mixes, varying 28 day design strength (10, 20, 30, 40, 50 MPa), percentage of PFA as part cement replacement (OPC only, 15% PFA, 30% PFA, 50% PFA and 70% PFA) and the coarse aggregate content to give under-, average- and over-sanded mixes. Over this wide range of mixes, the fresh properties and development of the compressive strength were observed. Secondly, properties affecting pavement quality concrete were observed on a similar range of mixes. These properties were flexural strength, surface wear resistance by wire brush, sand blasting and ball race abrasion and the drying shrinkage.